Stimulus-Organism-Response Dynamics in Short-Form Video Commerce: Perceived Authenticity, Hedonic Motivation, and Impulse Buying Among TikTok Shop Users - Diana Agustina; Ayuningtyas Yuli Hapsari (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
Indonesia is among the fastest-growing social commerce markets globally, with TikTok Shop serving as the dominant platform for impulsive skincare purchasing. Despite growing scholarly interest in social commerce, qualitative understanding of how consumers subjectively experience and interpret authenticity cues and hedonic motivations during impulsive buying remains limited. This study employs a qualitative phenomenological approach to investigate the lived experiences of 20 purposively selected Indonesian TikTok Shop users. Data were collected through in-depth semi-structured interviews, structured observations, and documentation over an eight-month fieldwork period, then analyzed using Miles and Huberman's interactive model alongside phenomenological thematic analysis. Findings reveal that participants perceived authenticity across source, message, and relationship dimensions as a trust-generating mechanism that lowers psychological barriers to spontaneous purchasing. Hedonic motivations adventure, social, gratification, and role-playing were experienced as emotionally activating forces driving impulsive decisions. Critically, participants described an experiential interplay in which authenticity amplifies hedonic responses and hedonic platform states heighten receptivity to authenticity cues. These findings enrich understanding of the Stimulus-Organism-Response (SOR) framework in social commerce by illuminating the experiential mechanisms underlying consumer impulse behavior in short-form video environments.